KOMPONEN METABOLIT SEKUNDER DAN AKTIVITAS ANTIOKSIDAN Spirulina fusiformis YANG DIKULTUR PADA MEDIA CAMPURAN (PUPUK R1, UREA DAN KATALIS) - Nabila Ukhty (JURNAL PERIKANAN TROPIS, 2018)
Spirulina fusiformis is one of blue algae which can produce phycocyanin pigments. In this study used a mixed media consists of fertilizer R1, urea and catalyst as a medium for microalgae growth. This study aims to determine the growth rate, secondary metabolite component and antioxidant activity of S. fusiformis which was cultivated in a mixture media cnsists of fetilizer R1, urea and catalysts. S. fusiformis was cultured for 21 days. Based on the results of the study, it is known that S. fusiformis culture experienced five stages of growth. The logarithmic phase occurs on the 3rd day until the 10th day, the stationary phase occurs on the 10th day to the 15th day, and the death phase occurs on the 20th day. S. fusiformis biomass harvested on the 12th day contained alkaloids, flavonoids, saponins and steroids. The biomass antioxidant activity of S. fusiformis harvested on the 12th day had IC50 tilapia of 1937.41 ppm.